Regular Medical Ethics Education Through Problem Based Learning - Saambhavi; Ahmad, Ayesha; MMA Faridi; Singh, Amrita (Asian Journal of Medical Research, 2023)
The Global Community has been humbled yet again by the tragic emergence of a new disease in the form of Covid-19 leading to the refocusing of spotlight upon areas of Health, Immunity, Hygiene, Diagnosis, Cure, Research on Cause & Cure of Diseases, Investment in these areas by relevant bodies and Importance of Human Life overall. This Global Community without any exception of rich or poor, developed or 3rd World has had to bear the burden of medical helplessness owing to unprecedented demand of resources. ELMCH being a Covid dedicated hospital saw multiple impacts of these seminars & learnings coming out of the discussions. With these seminars ongoing a feedback from the participants were taken regarding the knowledge of the pillars of medical ethics with the help of multiple choice questionnaire and it was seen that 90 % of the participants had the awareness of the concept of ethics. Taking a look at the pandemic through the perspective of verse, music, role plays and skits, medical care workers were able to communicate their encounters of outrage, being over troubled, burn out and despite not being able to withstand each and everyone’s issue, reacted with refkections, sympathy, humankind and compassion.